2011
DOI: 10.1016/j.exppara.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of permethrin in salivary glands of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) semi-engorged females

Abstract: Because of the medical and veterinary importance of ticks and the wide use of synthetic chemical substances such as permethrin (active ingredient of Advantage® Max3 - Bayer)for their control, this study evaluated the effects of different concentrations (206, 1031 and 2062 ppm) of the acaricide on the salivary glands of Rhipicephalus sanguineus semi-engorged females. Results showed that permethrin is a potent substance that acts morpho-physiologically in the tick glandular tissue, causing changes in the acini s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 30 publications
10
25
0
Order By: Relevance
“…In this study, the presence of myelin figures and lysosomes (structures that should only be observed in glands in more advanced stages of engorgement) was also observed. These data corroborate Nodari et al [16][17][18], who reported that permethrin would be accelerating the degeneration of the salivary glands of the R. sanguineus s. l. females subjected to different concentrations of the product.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, the presence of myelin figures and lysosomes (structures that should only be observed in glands in more advanced stages of engorgement) was also observed. These data corroborate Nodari et al [16][17][18], who reported that permethrin would be accelerating the degeneration of the salivary glands of the R. sanguineus s. l. females subjected to different concentrations of the product.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the ultrastructural and cytochemical data obtained in this study complement studies by Nodari et al [16][17][18], confirming the neurotoxic action [9], of permethrin. Even in lower concentrations than the ones commercially recommended, the product would act on the morphophysiology of the salivary emergent Life Sciences Research Nodari et al glands of R. sanguineus s. l. semi-engorged females, accelerating the degeneration process through atypical cell death, by apoptosis (fragmentation) and autophagy (vacuolation) simultaneously.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations